Long-term physical training in adolescent sprint and middle distance swimmers alters the composition of circulating T and NK cells which correlates with soluble ICAM-1 serum concentrations - Notbohm, H. L.; Schumann, M.; Fuhrmann, S.; Klocke, J.; Theurich, S.; Bloch, W. (European Journal of Applied Physiology, 2021)
Purpose: it remains unknown how different training intensities and volumes chronically impact circulating lymphocytes and cellular adhesion molecules. First, we aimed to monitor changes in NK and T cells over a training season and relate these to training load. Second, we analyzed effects of training differences between swimmers on these cells. Finally, we examined if changes in lymphocytes were associated with sICAM-1 concentrations. Methods: We analyzed weekly training volume, training intensity, proportions of T and NK cells and serum sICAM-1 in eight sprint (SS) and seven middle-distance swimmers (MID) at three points over a 16-week training period: at the start (t0), after 7 weeks of increased training load (t7) and after 16 weeks, including 5-day taper (t16). Results: Training volume of all swimmers was statistically higher and training intensity lower from t0-t7 compared to t7-t16 (p = 0.001). Secondly, training intensity was statistically higher in SS from t0-t7 (p = 0.004) and t7-t16 (p = 0.015), while MID had a statistically higher training volume from t7-t16 (p = 0.04). From t0-t7, NK (p = 0.06) and CD45RA+CD45RO+CD4+ cells (p < 0.001) statistically decreased, while CD45RA-CD45RO+CD4+ cells (p = 0.024) statistically increased. In a subgroup analysis, SS showed statistically larger increases in NK cells from t7-t16 than MID (p = 0.012). Lastly, sICAM-1 concentrations were associated with changes in CD45RA-CDRO+CD4+ cells (r = - 0.656, p = 0.08). Conclusion: These results indicate that intensified training in swimmers resulted in transient changes in T and NK cells. Further, NK cells are sensitive to high training volumes. Lastly, sICAM-1 concentrations may be associated with the migration and maturation of CD4+ cells in athletes.